MONETARY POLICY DYNAMICS IN NIGERIA: EMPIRICAL EVIDENCES FROM BAYESIAN VECTOR AUTOREGRESSION WITH STOCHASTIC VOLATILITY - Ojo, Oluwadare O.; Owonipa, Oluremi R. (FUDMA JOURNAL OF SCIENCES, 2024)
In this paper, we examine the dynamics of monetary policy in Nigeria with Bayesian approach to a vector autoregression (VAR). We construct and estimate Bayesian Vector Autoregression with Stochastic Volatility (BVAR-SV) model and extract important policy inputs from the model. Nigeria economy is unstable and it is a known fact that changes to monetary policy affects performance of some macroeconomic variables. The BVAR has the ability to capture sudden changes and nonlinearities arising from the interaction among macroeconomic variables and associated shocks. The study uses monthly data during the period 2003M01 till 2023M12 with three macroeconomic variables namely; inflation rate, money supply, and interest rate. A Markov Chain Monte Carlo algorithm that allows for Bayesian estimation and prediction is employed. Results show that there is strong evidence of monetary policy playing a significant role in explaining the dynamics of interest rate while the impulse responses for the variables to a monetary policy shock do change significantly over time. Also, the monetary policy exert less significant influence in terms of money supply and inflation than interest rate in explaining the dynamics in of monetary policy. It is recommended that BVAR should be also be extended to other macroeconomic variables to examine the effects on monetary policy dynamics.